Heterogeneous consumer preference for certified palm oil sustainability attributes: evidence from stated preference survey - Dauda, Suleiman Alhaji; Sidique, Shaufique Fahmi; Tey, Yeong Sheng; Djama, Marcel (Sciendo, 2022)
Consumers’ concern on the adverse effect of the palm oil have contributed towards setting sustainability standard and certification of the palm oil. Choice experiment study was conducted to evaluate consumers’ preference for sustainable palm oil supply chain model with environmental attributes. There is allegation that oil palm expansion has threatened biodiversity, and has led to increase in the emission of harmful CO2. Certified sustainable palm oil was introduced to stimulate consumer demand for conservation graded palm oil products. We examine consumer awareness on palm oil and their heterogeneous preference for cooking oil certified by Round table on Sustainable Palm Oil. Sample of 322 consumers were surveyed in Malaysia. Respondents were found to be aware of the importance of palm oil and its contribution of to the economy. We analysed Latent Class Model with 2 classes, the 1st class are “concerned consumers” who are willing to pay up to 5% price premium increase over the present stock value of cooking oil. While 2nd class are “palm oil neutral” who are willing to pay 1%. Income level of the consumers and education were found to have positively influenced their preference for sustainable palm value chain and environmental attributes. Thus, adoption of certification and ecolabel of the palm oil will promote sustainability, also the price premium will incentivise RSPO value stakeholders to conserve biodiversity and minimise CO2 emission, on demand side, it will stimulate consumers to switch to the consumption of sustainable palm oil.